Konsep Deep Learning dalam Perspektif Nilai-Nilai Ki Hajar Dewantara - Ardika Dewa Nugroho; Muhammad Jaatsiy Abdillah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research analyzes the concept of deep learning in education through the philosophical values of Ki Hajar De-wantara. Utilizing a qualitative literature study, it explores the connection between deep learning, Indonesian hu-manistic values, and local wisdom. The findings reveal that Dewantara's